Case report: Malignant chemodectoma with hepatic metastasis in a cat - Adetunji, Shakirat Adeola; Chen, Kaiwen; Thomason, Justin; Matias Ferreyra, Franco (Frontiers in Veterinary Science, 2023)
A 10-year-old, male-neutered, domestic short-hair cat was examined at the Veterinary Health Center Emergency Service at Kansas State University for a one-day history of dyspnea. Prior to thoracocentesis, sedation was provided. The cat stopped breathing after sedation and went into cardiac arrest. Cardiopulmonary resuscitation (CPR) was unsuccessful. At necropsy, there was severe pleural effusion and bilateral pulmonary atelectasis. The myocardium of the atria and ventricles, and tunica adventitia of coronary vessels, pulmonary artery, and aorta, had pale, firm, multinodular masses ranging from 0.3 -0.5 cm in diameter. Multiple nodules were also present in the liver. Multifocally expanding the epicardial fat and compressing the underlying epicardium, infiltrating, and expanding the myocardium, and expanding the walls of major vessels, there was a multinodular, unencapsulated, densely cellular neoplasm composed of polygonal epithelial cells arranged in nests and packets and supported by a fine fibrovascular stroma. The nodules in the liver had similar histologic features. In this case, neoplastic cells at the primary and metastatic sites were intensely immunoreactive to synaptophysin, variably reactive to chromogranin A, and negative for neuron specific enolase, cytokeratin, vimentin, thyroglobulin, and smooth muscle actin. The gross, histologic, and immunohistochemical findings support the diagnosis of chemodectoma, with metastases to the liver. Synaptophysin and chromogranin A were the most useful immunohistochemical markers to diagnose malignant chemodectoma in this cat.